Location selection methodology for data center with renewable energy integration - Ayyildiz, Ertugrul; Yildirim, Betul; Aydin, Nezir; Yıldırım, Betül (Elsevier Ltd., 2025)
With the development of technology, dependence on the Internet has increased the demand for data centers. However, selecting optimal locations for data centers remains a critical challenge due to the need for energy efficiency and environmental sustainability. This study addresses this research gap by proposing a novel decision-making framework that integrates renewable energy considerations into the data center site selection process. The main objective is to identify the most suitable locations for data centers by evaluating multiple criteria. Expert-based evaluations are collected and processed using the Picture-Fuzzy SWARA (PiF-SWARA) method to determine the relative importance of criteria, providing a robust weighting mechanism. The Picture-Fuzzy VIKOR (PiF-VIKOR) method is then applied to rank six potential data center locations in Türkiye. This study is the first to combine PiF-SWARA and PiF-VIKOR in the context of renewable energy-integrated data center siting, offering a novel and comprehensive decision-making approach. Findings indicate that locations with high solar and wind energy potential, coupled with strong infrastructure accessibility, offer the most viable solutions. As the first study to integrate the PiF-SWARA and PiF-VIKOR methods for data center site selection, this research contributes to developing sustainable infrastructure and offers a replicable framework for future studies. © 2025 Elsevier Ltd
Keywords: Data centers; Multi-criteria decision making; Picture fuzzy set renewable energy; Site selection